АКТГ-ектопічний синдром, обумовлений бронхіальним карциноїдом - Ляшук, П. М.; Станкова, Н. І.; Оленович, О. А.; Ляшук, Р. П. (Clinical Endocrinology and Endocrine Surgery, 2012)
A case of Cushing’s syndrome due to ACTH-lung tumor is described with clinically dominating rare thromboembolic syndrome along with typical symptoms. Surgical ablation of bronchial carcinoid resulted in abatement of clinical cushingoid symptoms.